Respuesta :
6(x-1) = 9(x+2)
Use distributive property on both sides:
6x-6 = 9x + 18
Subtract 6x from both sides:
-6 = 3x + 18
Subtract 18 from both sides:
-24 = 3x
Divide both sides by 3:
X = -8
Answer:
x=−8
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
6*(x-1)-(9*(x+2))=0
(6 • (x - 1)) - 9 • (x + 2) = 0
6 • (x - 1) - 9 • (x + 2) = 0
Pull out like factors :
-3x - 24 = -3 • (x + 8)
-3 • (x + 8) = 0
Solve : -3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solve : x+8 = 0
Subtract 8 from both sides of the equation :
x = -8